Performance-Based Seismic Analysis and Design of a Mid-Rise RC Guest House in a High Seismic Zone of Indonesia - Harto Nurbian; Agyanata Tua Munthe; Syafwandi; Agung Sumarno (Marasofi International Media and Publishing (MIMP), 2025)
This study presents the seismic-resistant structural design of a 3-storey guest house with a roof garden, located in Surabaya, Indonesia, an area classified as Earthquake Zone 6. The building is designed using a Special Moment Resisting Frame System (SMRFS) as per SNI 1726:2019, which is appropriate for high seismic risk areas. The equivalent static lateral force method is employed for seismic analysis. Structural modeling and upper-structure design are performed using ETABS, while sub-structure components such as pile caps and foundations are analyzed manually and supported by PCA Column software. The structural elements are designed according to Indonesian codes, including SNI 2847:2019 for reinforced concrete, SNI 1727:2020 for minimum loads, and SNI 2052:2017 for steel reinforcement. The final design yields column dimensions ranging from 200×400 mm to 600×600 mm and beam dimensions from 250×400 mm to 350×700 mm, with slab thicknesses of 120 mm and 150 mm. The results confirm that the structure meets strength, stiffness, and ductility requirements. This research ensures compliance with national standards while enhancing structural safety in high seismic zones.